Comparative metabolism of conjugated and unconjugated pterins in Crithidia, Leishmania and African trypanosomes - Ong, Han B.; Wyllie, Susan; Fairlamb, Alan H. (PLOS Neglected Tropical Diseases, 2025)
Mammalian cells synthesise tetrahydrobiopterin de novo, an essential cofactor for hydroxylation of aromatic amino acids, cleavage of ether lipids and the synthesis of nitric oxide. In contrast, kinetoplastid parasites are pterin auxotrophs and none of the above metabolic functions can account for the essential requirement of an unconjugated pterin for growth. Here we investigate the pterin requirements for growth and survival of two medically important parasites (T. brucei and L. major) in comparison with the model insect parasite, Crithidia fasciculata. The pterin concentration required to support 50% of maximum growth of each parasite was determined in defined pterin-free media for a variety of naturally occurring pterins. T. brucei and C. fasciculata showed an identical order of preference with the most active being 6-biopterin, followed by dihydrobiopterin > tetrahydrobiopterin > L-neopterin > sepiapterin. In contrast, L. major showed a pronounced growth preference (>200-fold) for the reduced pterins over the the oxidised forms 6-biopterin and L-neopterin. The unnatural isomers 7-biopterin or D-neopterin supported growth poorly, or not at all, in these organisms. Other pterins were inactive. HPLC analysis of pterins supporting growth established that these were metabolised to the tetrahydro-forms (>95%) with no evidence of further interconversion. In the absence of pterins, the parasites failed to grow and lost viability with <1% surviving beyond 5–14 days. Relatively high concentrations of folate or dihydrofolate (>500 nM) could support growth in the absence of unconjugated pterin and HPLC analysis identified pteridoxamine and 6-hydroxymethylpterin (as tetrahydro-form) in cell extracts. A common feature of pterins that support growth is the presence of at least one or more linear carbon substituents at position 6 of the pteridine ring with at least one hydroxyl group, ideally in the 1S configuration. The possible essential roles of these important metabolites are discussed.